Differences in fear response strategy and stress susceptibility amongst four different commercial layer strains reared cage free - Brown, Austin A.; Sobotik, Eric B.; House, Gabrielle M.; Nelson, Jill R.; Archer, Gregory S. (Frontiers in Physiology, 2022)
Different commercial lines of laying hens may show varying levels of fearfulness in response to stressful events or situations. It is important to understand the differences in fear response and stress susceptibility. In this study, four commercial laying hen lines reared from hatch to 32 weeks of age in a cage free system Strains consisted of a brown egg laying line (Hyline Brown; HB) and three white egg laying lines (W36, W80, and LSL). Sixty hens from each strain were used. Each hen was assessed for fearfulness using the following tests: isolation (ISO), emergence (EMG), inversion (INV), and tonic immobility (TI). Stress was assessed based on physical asymmetry (ASYM), corticosterone (CORT) concentrations, and heterophil:lymphocyte ratio (HL). At 3 weeks of age, the W80 birds exhibited more vocalizations during ISO and a shorter duration to emerge than other lines except the HB birds during EMG. Conversely the W36 birds had fewer vocalizations during ISO and emerged quicker than other birds except the LSL during EMG. At 16 weeks of age, the LSL and the W36 bird demonstrated greater fear in TI than the HB. At 30 weeks of age, the observed fear response strategies of each strain changed from previous age and differences were observed between lines (P < 0.05). At both 16 and 30 weeks of age the HB birds had the highest (P < 0.05) stress indicators (CORT, HL, and ASYM). Furthermore, they had a higher CORT after acute stressor (P < 0.05). Commercial lines of laying hens show clear variation in their stress response strategy and stress susceptibility. Brown egg laying hens tend to actively avoid perceived threats whereas white egg laying hens use passive avoidance. Brown egg laying hens also have higher levels in the measures of stress susceptibility than white egg laying hens. Understanding of individual strain response to fearful stimuli and other stressors will help to design breeding strategies to maximize hen welfare and assessment and further increase their success in alternative housing systems.